Charecterization Of Partially Purified Trypsin Inhibitor From Lablab Purpureus - ANIL S. KHANDAGALE; ADITI A. PATTEWAR; LAXMIKANT H. KAMBLE (International Journal of Pharma and Bio Sciences, 2015)
Lablab purpureus is a protein rich crop plant belonging to the family Leguuminosae. A proteinacious inhibitor of trypsin (LPTI) was isolated from Lablab purpureus seeds. Protein was extracted in 0.1 M tris–Cl buffer (pH-8.0) and subjected to precipitation using 20% ammonium sulphate, dialyzed against 0.1M phosphate buffer and further purified by using DEAE cellulose column. Fold purification obtained was 12.0 of LPTI. Three isoforms of LPTI were observed in gelatin embedded native PAGE. SDS-PAGE analysis of Lablab purpureus seed extract eluted from DEAE cellulose column showed three polypeptide bands of 30.1 kDa, 20.6 kDa and 17.9 kDa. Solution assay with casein showed 36 mg of inhibitor concentration causes 50% inhibition of trypsin. Thermo stability study showed that the LPTI are quit thermostable, it lost its complete activity when heated at 100°C for 90 minutes. Inhibitors are stable between pH 6.to 8.